2021
DOI: 10.3390/pharmaceutics13040480
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid System for Local Drug Delivery and Magnetic Hyperthermia Based on SPIONs Loaded with Doxorubicin and Epirubicin

Abstract: Cancer is one of the most common causes of death worldwide, thus new solutions in anticancer therapies are highly sought after. In this work, superparamagnetic iron oxide nanoparticles (SPIONs) conjugated with anticancer drugs are synthesized and investigated as potential magnetic drug nanocarriers for local drug delivery and mild magnetic hyperthermia. We have obtained a hybrid system loaded with holmium and anticancer drugs and thoroughly studied it with respect to the size, morphology, surface modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…By contrast, but in agreement with our results, it has been reported that chemotherapeutic agents (DOX or epirubicin) were more efficient than those synthesized with NPs [ 29 , 30 ]. Variations in the results may be due to different cancer cells used or some fluctuations in the DOX amount conjugated to AuNPs.…”
Section: Resultssupporting
confidence: 94%
“…By contrast, but in agreement with our results, it has been reported that chemotherapeutic agents (DOX or epirubicin) were more efficient than those synthesized with NPs [ 29 , 30 ]. Variations in the results may be due to different cancer cells used or some fluctuations in the DOX amount conjugated to AuNPs.…”
Section: Resultssupporting
confidence: 94%
“…Fe 3 O 4 nanoparticles (NPs) are not only the preferred materials for magnetic targeting due to their high saturation magnetization [18][19][20][21][22][23], but also the focus of research on their chemical kinetic properties [24,25]. Fe 3 O 4 NPs have good internal stability and have been shown to be non-cytotoxic at neutral pH [26].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works regarding magnetic NPs for magnetic hyperthermia, we found SAR values to be in a similar range (105–225 W/g) for lanthanide-doped IONPs [ 46 ]. Previously synthesized NPs doped with holmium were characterized by SAR values as high as 350 W/g for trastuzumab-modified SPIONs [ 47 ], 400 W/g for core–shell SPIONs trastuzumab bioconjugates [ 48 ], and 370 W/g for doxorubicin/epirubicin-modified SPION [ 49 ]. The SAR value itself (apart from a dependency on AMF frequency and field amplitude) is connected to the NPs’ size, shape, core modification, ligand attachment, and their amount.…”
Section: Resultsmentioning
confidence: 99%